INFLUENCING FACTOR ANALYSIS OF FATIGUE CRACK INITIATION LIFE ON CRANE LATTICE BOOM - CAI FuHai; YUAN WeiChen; WANG Xin; ZHAO FuLing; JIA XingJun (Jixie qiangdu)
The crane lattice boom is complex and the load is diversity,part of the structure may suffer plastic deformation because of the high stress concentration or poor weld quality under exceptional poor load conditions. So using strain analysis parameter is reasonable compared to stress parameter. The paper was focused on the fatigue crack initiation stage of crane lattice boom. The method of local stress strain was used combined with the correction Neuber method. A crane fatigue crack initiation life evaluation algorithm model was built. According to the model,three main factors which will influence the initiation life calculation were analyzed and compared. Fatigue tests were also carried out with K nodes of crane lattice boom. When the material was determined under certain circumstances,the stress concentration factor had the most impact result on the life. The mean stress on the material had the less impact but it cannot be ignored. According to the Factors,optimization suggestions to lattice boom spatial structure and work process improvement measures were proposed.